DIFFERENT APPROACHES TO THE DEFINITION OF THE CONCEPT INTELLECTUAL AND LOGICAL SKILLS ”IN SCIENTIFIC LITERATURE - Lavreshyna, H.Yu. (Pedagogy of Higher and Secondary Education, 2002)
In the article intellectual-logical skills are regarded as an index of logical culture o f pupils.